Disentangling Culture and Religion: A Comparative Analysis of Cultural and Religious Personality Constructs - Karki, Tej Bahadur; Shrestha, Diwat Kumar; Kunwar, Mala (NPRC Journal of Multidisciplinary Research, 2025)
Background: Personality psychology is shaped by both cultural and religious influences. While often intertwined, the distinct conceptual foundations of cultural personality (arising from shared societal norms and ecological pressures) and religious personality (stemming from individual beliefs, practices, and doctrinal adherence) require clearer delineation to avoid conflation in research and practice. Objective: This paper aims to systematically contrast cultural personality with religious personality by synthesizing empirical findings and proposing conceptual distinctions, with the goal of clarifying their unique and overlapping influences on individual differences. Methods: A systematic review of literature was conducted, drawing from peer-reviewed articles, books, and empirical studies identified through database searches. The analysis focused on recent publications (post-2010) utilizing validated personality models and religiosity measurements to extract and compare thematic content, theoretical frameworks, and methodological approaches. Findings: The review confirms that cultural and religious personality are related yet distinct constructs. Cultural personality operates primarily at a population level, shaping broad trait distributions (e.g., collectivism promoting agreeableness). Religious personality functions at the individual level, showing consistent, albeit modest, associations with traits like Agreeableness and Conscientiousness. While religion often acts as a cultural subsystem, the two diverge in their primary causal mechanisms—cultural personality from ecological and institutional pressures, and religious personality from doctrinal learning and existential concerns. Conclusion: Cultural and religious personalities represent different levels of explanation and are driven by distinct mechanisms. An integrated yet differentiated understanding is crucial for accurate psychological assessment and theory. Implication: Recognizing this distinction is vital for cross-cultural research, clinical practice, and organizational policy, as it prevents misattribution of behavior and allows for more nuanced interventions that respect the separate influences of cultural context and religious identity.